The ROLE OF FINANCIAL LITERACY, ACCESS, AND MANAGEMENT SKILLS IN SHAPING MARITAL SATISFACTION - Utami, Cahyaning Budi (Journal of Business Studies and Management Review, 2025)
Economic challenges are the second leading cause of divorce in Indonesia. Based on Couple and Finance Theory, marital satisfaction is influenced by personal factors and financial capabilities. This study aims to examine the impact of financial literacy and financial access on marital satisfaction, with a focus on the moderating role of financial management skills. A quantitative approach was applied, and data were analyzed using structural equation model, resulting 670 valid responses. The findings reveal that financial literacy and financial access directly influence financial management skills enhance the effect of financial literacy and financial access on marital satisfaction indirectly. These results underscore the importance of improving financial management skills to promote marital satisfaction through better financial practices. Additionally, integrating financial education into premarital programs for prospective couples is essential to strengthen financial ability and foster marital satisfaction.